Factors predicting repeated ablation in ventricular tachycardia patients. (19th May 2022) - Komlosi, F; Toth, P; Vamosi, P; Szegedi, N; Sallo, Z; Piros, K; Perge, P; Osztheimer, I; Abraham, P; Szeplaki, G; Merkely, B; Geller, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Heart Program Background: Catheter ablation has emerged to be the principal treatment for recurrent ventricular tachycardia (VT). Previously, several predictors of VT recurrence have been described, such as LVESD, severe MR, incessant VT, ICD shocks and elevated LDH levels. However, factors predicting an additional ablation are unknown. Purpose: We aimed to establish predictors of repeat ablation and compare to the predictors of ventricular arrhythmia recurrence during 1-year follow-up in structural heart disease. Methods: Baseline medical history, laboratory results, imaging parameters, clinical properties of VTs, and procedural data were gathered in a structured database. Results: Out of the 272 patients, 96 (35%) experienced recurrence and 36 (13%) had repeated procedures within 1 year. Independent predictors of recurrence were left ventricular end systolic diameter (HR = 1.516, p=0.015), severe mitral regurgitation (HR = 2.446, p = 0.002), incessant VT (HR = 1.64, p = 0.02), VT inducibility (HR = 3.71, p = 0.003), ICD shocks (HR = 1.95, p = 0.002) and elevated LDH levels (HR = 1.26, p = 0.003). Regarding redo ablation, elevated LDH level (HR = 1.64, p = 0.01), incessant VT (HR = 2.94, p < 0.001), ICD shocks (HR = 2.38, p = 0.02), only exit point ablation (HR = 2.14, p = 0.023) were independent predictors, while hypertension (HR = 0.32, p = 0.03), longer transmitral E-wave deceleration time (HR = 0.47, p = 0.04), substrate modification (HR = 0.47, p = 0.044) were protective. Conclusion: Predictors of repeat ablation overlap only partially with those of VT recurrence. Predictors implying higher risk VT episodes predict both recurrence and repeat ablation while factors associated with more severe left ventricular systolic dysfunction predict recurrence but not a redo procedure.